Exploring Single Women's Affect, Behavior, and Cognition toward Singlehood and Marriage. - Almodiel, Keth G., et al.; De Veyra, Princess L.; Tandez, Gezella N. (Tacloban City Keth G. Almodiel, 2012)
This research is a qualitative study on the life of single women in selected areas in Leyte specifically in Baybay, Carigara, Jaro, Palo, Tabontabon and Tacloban. The twelve (12) single women participants aged 40-70 were distinguished through purposive sampling, in which an interview schedule was utilized by the researchers. This study aimed to find out the affect, behavior, and cognition of these single women toward singlehood and marriage. It is to know if it is their choice or not to remain single. Results showed that most single women responded that it was their choice while others said they were driven by fate. A choice or not, their status at present was the result of certain circumstances that happened to them in the past. Results also indicated that singlehood has its advantages as well as disadvantages, and there are also stereotypes that the society holds about them. But this does not mean that they are not happy, satisfied, and fulfilled with their lives. Single women are not alone and lonely. They are not bitter persons. In fact, their views on marriage are positive and they know a lot of things about marriage even though they are not married. The researchers believe that the conduct of this study will serve as awareness among other sectors of the society regarding their stereotypes and misconceptions that degrade these women.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: Social Science